2011
DOI: 10.1007/s12010-011-9434-5
|View full text |Cite
|
Sign up to set email alerts
|

Additional Paper Waste in Pulping Sludge for Biohydrogen Production by Heat-Shocked Sludge

Abstract: Dark anaerobic fermentation is an interesting alternative method for producing biohydrogen (H(2)) as a renewable fuel because of its low cost and various usable organic substrates. Pulping sludge from wastewater treatment containing plentiful cellulosic substrate could be feasibly utilized for H(2) production by dark fermentation. The objective of this study was to investigate the optimal proportion of pulping sludge to paper waste, the optimal initial pH, and the optimal ratio of carbon and nitrogen (C/N) for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 36 publications
(33 reference statements)
1
5
0
Order By: Relevance
“…Wan et al observed acetate-type fermentation when the hydrolysate of waste-activated sludge was used as the substrate . Chairattanamanokorn et al obtained the acetate-type fermentation when the C/N ratio was adjusted to 40 . In our previous study, the change of fermentation type from butyrate to acetate was observed when glucose was added to γ-irradiation-treated sludge .…”
Section: Resultsmentioning
confidence: 83%
See 1 more Smart Citation
“…Wan et al observed acetate-type fermentation when the hydrolysate of waste-activated sludge was used as the substrate . Chairattanamanokorn et al obtained the acetate-type fermentation when the C/N ratio was adjusted to 40 . In our previous study, the change of fermentation type from butyrate to acetate was observed when glucose was added to γ-irradiation-treated sludge .…”
Section: Resultsmentioning
confidence: 83%
“…55 Chairattanamanokorn et al obtained the acetatetype fermentation when the C/N ratio was adjusted to 40. 56 In our previous study, the change of fermentation type from butyrate to acetate was observed when glucose was added to γirradiation-treated sludge. 35 Thus, it can be seen that acetatetype fermentation was more likely to happen when polysaccharides were used as the main carbon source for hydrogen production.…”
Section: Energy and Fuelsmentioning
confidence: 95%
“…So, the organosolv pretreatment is an emergent area worth exploring because lower amounts of inhibitory compounds are generated than with dilute acid pretreatment . However, ethanol is an inhibitor for the hydrolytic process, so it is necessary to remove the traces of alcohol . One of the advantages of organosolv is the relatively easy recovery of the organic solvents by distillation and their recycling in the process.…”
Section: Classification Of Pretreatmentsmentioning
confidence: 99%
“…The process has been proven at full scale; the investment cost is one of the lowest among pretreatments . It is applicable to a great variety of substrates (corn stover, pulp and paper sludge, food wastes and high sugar yields) or relatively high gas biofuels yields can be obtained (Table ). However, in some work the presence of phenolic compounds such as coniferylaldheyde has been observed; for instance, after the pretreatment of Norway spruce by Larsson et al 0.2 mmol L −1 of this compound was found after the treatment of biomass by NaOH.…”
Section: Enzymatic or Biological Pretreatmentsmentioning
confidence: 99%
“…Fortunately, paperboard mill wastewater (PMW) can be considered as a potential source for generation of renewable bioenergies in the form of methane and/or hydrogen via anaerobic digestion process . However, PMW mainly comprises complex compounds such as cellulose, hemicellulose, and lignin, which are recalcitrant to microbial and enzymatic action . Moreover, spillage of biocides, oil, dyes, acids, etc., in the PMW will certainly reduce the activity of consortium anaerobic bacteria .…”
Section: Introductionmentioning
confidence: 99%